Pembuatan Company Profile Dinamis dengan PHP dan MYSQL (Studi Kasus : Hima Informatika Digitech University) - Akik Jainul Hak; Fahmi Abdullah (Journal of Information Technology, 2024)
In today's digital era, the presence of a dynamic Company Profile is crucial in introducing and promoting the identity of an organization. This research aims to create a dynamic Company Profile using PHP and mysql as a case study of HIMA Informatika Digitech University. Through this approach, the steps of creating the system will be discussed, including database design with mysql to store company information, as well as the implementation of dynamic functionality using PHP to allow efficient content updates. The development method used will include requirements analysis, system design, implementation, and testing. The results of this research are expected to contribute to understanding the implementation of dynamic web technology in the context of creating a company profile as well as providing practical guidance for organizations that want to convey their information through online media.